أسباب الكذب عند الأطفال من وجھة نظرالمعلمین (Journal of the College of Education for Women, 2019)
The current research tries to study the reasons for lying since itsinception, as it is interesting to a child's moral growth, which can benefit fromthe results of this research by institutions of socialization, parents andteachers in the treatment and care of children.The objective of this research is to highlight the reasons for lying to thechildren from the viewpoint of teachers and the answer to the paragraphs ofresearch designed research instrument (questionnaire) was distributed to asample of teachers was clear from the analysis that the reasons lie thatreceived a high percentage of members of the sample are: -- The fear of severe punishment- Child rid himself of a specific problem- To satisfy the parents- The desire of the child to an adult to encourage and reward- Keep up the child to his friends and to win the raid- To get sympathy and pity- The child's desire to attract the attention of his other- Depriving the child from enjoying life verse lies for compensation- Access to the high status of others- Excessive indulgence of the child by others- Neglecting the family of the childThe research came out with several recommendations and proposals